Antagonistic effect of Malaysian isolates of trichoderma harzianum and gliocladium virens on sclerotium rolfsii - J., Jomduang; Meon, Sariah (Universiti Putra Malaysia Press, 1997)
Trichoderma harzianum and Gliocladium virens isolated from parasitized sclerotia were evaluated for their antagonistic potential against Sclerotium rolfsii. Based on the mechanisms ofantagonism in vitro, dual culture and colony degradation tests, hyphal interaction, antibiosis and parasitism of sclerotia, both antagonists were found to be effective against S. rolfsii. However, G. virens was more effective than T. harzianum in dual culture and colony degradation tests. Under SEM, both antagonists colonized, penetrated and sporulated inside the sclerotia of the test pathogen, suggesting parasitism of sclerotia could be the principal mechanism involved. T. harzianum and G. virens were comparable in their antibiosis activity. In addition, they can co-exist together and are synergistic in activity when tested simultaneously in dual culture.